Uma proposta de método para melhoria de desempenho do codificador x264 baseada na análise do acesso ao barramento externo de memória - Duma, Luiz Henrique (2011)
This study attempts to systematize the use of techniques to reduce access to external memory (RAM) for the x264 encoder, as well the use of software profiling tools with focus on the usage of hardware performance counters (HPC), available in many modern processors. The results show up a reduction between 16% and 18% for execution time of the encoder, without noticeable changes on objective video quality metrics. Digital video coding is an essential resource to produce video for Internet, TV, and other media. Through video coding, it is possible to improve storage and bandwidth utilization for transmission and reception of video streams. On embedded devices, hardware resources impact on the encoder performance, for example, in video cameras of cellphones. This study analyzes the external memory access (RAM) at the x264 encoder implementation, aiming to identify ways to improve the encoding process performance. With software profiling tools and encoder performance analysis was possible to establish a data analysis method which results can be used to improve the overall encoder performance. The method implementation results show an improvement of 16% to 18% over a non-optimized encoder while keeping the same video quality measured from objective metrics.